The Strategic Role of School Principals in Enhancing Teacher Professionalism - Saputro, Yusdhiyanto Nugroho (Nur Science Institute, 2024)
Background: This study aims to: (1) Describe the principal's efforts in developing teacher professional competence at Muhammadiyah Baturan Elementary School. (2) Describe the obstacles in developing teacher professional competence at Muhammadiyah Baturan Elementary School. (3) Describe solutions in developing teacher professional competence at Muhammadiyah Baturan Elementary School. Method: This research is a qualitative research. Data collection techniques are carried out by interview, observation and documentation. Data validity techniques use method triangulation and source triangulation. Result: Research results: (1) The principal's efforts are: a. As a manager, he does not have the right strategy to empower teachers. b. As an administrator, he has not maximized his efforts in various activities of managing school program administration. c. As a supervisor, he has not maximized his efforts in evaluating teachers to find out their weaknesses and strengths when implementing learning. d. As a leader, he has the responsibility to mobilize all resources available in the school. (2) The principal's obstacles are: a. Senior teachers easily forget to master ICT media. b. Limited funding sources and infrastructure. (3) The principal's solutions are: a. The principal holds training on information and communication technology. b. The principal encourages to continue to develop and utilize existing facilities independently, including in training